Clinical Pharmacology - P N Bennett (Churchill Livingstone/Elsevier, 2008)
This book is for students, doctors and indeed for all concerned with evidence-based drug therapy. A knowledge of pharmacological and therapeutic principles is essential if drugs/medicines are to be used safely and effectively for increasingly informed and critical patients. Doctors who understand how drugs get into the body, how they produce their effects, what happens to them in the body, and how evidence of their therapeutic effect is assessed, will choose drugs more skilfully, and use them more successfully than those who do not.The principles involved are neither so numerous nor so difficult to understand as to deter any prescriber, including those whose primary interests lie elsewhere than in pharmacology. All who use drugs cannot escape either the moral or the legal \\\'duty of care\\\' to prescribe in an informed and responsible way.